Structural basis of the dynamic human CEACAM1 monomer-dimer equilibrium - Amit K. Gandhi (Nature Portfolio, 2021)
To understand how hCEACAM1 transitions between monomeric and dimeric states that are required for its activity, Gandhi et al. investigate hCEACAM1 homodimeric, monomeric, and transition states and their behavior in solution. This study suggests the flexibility of the GFCC’ face and its role in governing the formation of hCEACAM1 dimers and selective heterodimers.